Internal freezing and heat loss of apple (Malus domestica Borkh.) and sweet cherry (Prunus avium L.) reproductive buds are decreased with cellulose nanocrystal dispersions - Arnoldussen, Brent; Alhamid, Jassim; Wang, Peipei; Mo, Changki; Zhang, Xiao; Zhang, Qin; Whiting, Matthew (Frontiers in Plant Science, 2022)
Cold damage has caused more economic losses to fruit crop growers in the U.S. than any other weather hazard, making it a perennial concern for producers. Cellulose nanocrystals (CNC) represent a new generation of renewable bio-nanomaterials, with many unique physical and chemical properties, including their low thermal conductivity. Our team has developed a process for creating CNC dispersions that can be sprayed onto woody perennial crops, forming a thin insulating film around buds which has been shown to increase cold tolerance. Using digital scanning calorimetry (DSC) on dormant apple (Malus domestica Borkh.) reproductive buds, we investigated the thermodynamic properties of plant materials treated with CNC dispersion at lower temperatures. Scanning electron microscopy (SEM) was used to evaluate the thickness of CNC films and their deposition on the sweet cherry bud surface. Apple buds treated with 3% CNC exhibited lethal freezing at a temperature of 3.2 °C and 5.5 °C lower than the untreated control when sampled 1 and 3 days after application, respectively. Additionally, the latent heat capacity (J/g) of 3% CNC treated buds was 46% higher compared to untreated buds one day after application, and this difference increased by three days post application to 168% higher. The emissivity of cherry buds treated with 3% CNC was reduced by an average of 16% compared to untreated buds. SEM was able to detect the dried films on the surface of the buds three days after application. Film thickness measured with SEM increased with material concentration. The emissivity, HTE, and LTE results show that CNC-treated reproductive buds released thermal energy at a slower rate than untreated buds and, consequently exhibited internal ice nucleation events at temperatures as much as 5.5 ° C lower. The increased enthalpy during the LTE in the CNC-treated apple buds shows more energy released at lethal internal freezing. indicating that CNC coatings are increasing the amount of super-cooled water. The effects of CNC shown during the DSC tests were increased by CNC concentration and time post application. These results suggest CNC dispersions dry into nanofilms on the bud surface, which affects their thermodynamic processes at low temperatures